1986
DOI: 10.1111/j.1749-6632.1986.tb15998.x
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and Concentration of Steroid Hormones in Mammary Tissues

Abstract: In order to exert their biological effects, steroid hormones must enter the cells of target tissues and after binding to specific receptor molecules must remain for a prolonged period of time in the nucleus. Therefore the endogenous levels and the subcellular distribution of estradiol, estrone, DHEAS, DHEA ad 5-Adiol were measured in normal breast tissues and in malignant and nonmalignant breast tumors from pre- and postmenopausal women. For estradiol the highest tissue levels were found in the malignant sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1

Year Published

1987
1987
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 33 publications
1
18
1
Order By: Relevance
“…This delay in the peak concentrations of the estrogens explains the previously observed lack of correlation between serum and NAF estradiol (1, 2), which is seen again in the present study, and has been observed between serum and tissue concentrations of estradiol by others (3,5,11). However, the association between serum progesterone and NAF hormones has not been examined previously in detail.…”
Section: Discussioncontrasting
confidence: 35%
“…This delay in the peak concentrations of the estrogens explains the previously observed lack of correlation between serum and NAF estradiol (1, 2), which is seen again in the present study, and has been observed between serum and tissue concentrations of estradiol by others (3,5,11). However, the association between serum progesterone and NAF hormones has not been examined previously in detail.…”
Section: Discussioncontrasting
confidence: 35%
“…In a second study of 47 women the serum estradiol concentration at mid-luteal phase was similar (356t65.4 pmol/l), whereas in NAF it was lower (484t28 pmol/l) (Chatterton et al 2004). The latter value corresponds closely to concentrations of estradiol in tissue of premenopausal women when the tissue concentration is expressed in pmol/g (Thijssen et al 1986, Blankenstein et al 1999. There was no correlation between concentrations of DHEAS and ES in serum and those in NAF.…”
Section: Relationship Of Hormones In Naf To Concentrations Of the Hormentioning
confidence: 94%
“…In premenopausal women, however, all of the well established risk factors clearly implicate Es in the causation of BC (2)(3)(4)(5)(6). In this latter group, 17␤-estradiol (E 2 ) concentrations, all in the low picogram range, within narrow limits of serum and breast tissue levels (10)(11)(12)(13), are sufficient to increase sporadic BC risk. Therefore, it is essential to gain a better understanding of how Es, at these physiological concentrations, elicit their oncogenic effects in susceptible target tissues.…”
mentioning
confidence: 99%